(untitled) (Revista da Tulha, 2015)
This article presents some initial considerations on the James Wood’s composition Rogósânti. Written in 1986 for multiple percussion and dedicated to the percussionist Steven Schick, this piece is shaped into a large “tripartite route”, where the composer presents two main reasons based on rhythmic cells of Indian music. In this first stage of this analysis, we present some hypotheses concerning a possible “inspiration” linked to the concept of rhythmic characters of Oliver Messiaen.